Tribological properties of laser textured and DLC coated surfaces with solid lubricants - Oksanen, Jussi; Hakala, Timo; Tervakangas, Sanna; Kolehmainen, Jukka; Koskinen, Jari (International Conference on Plasma Surface Engineering, 2013)
Hydrogen free diamond-like carbon coatings (DLC), i.e. tetrahedral amorphous carbon (ta-C) films, have high hardness and low coefficient of friction at ambient temperature and humid conditions. However, the coefficient of friction and wear rate in sliding contacts against steel surfaces increase severely at elevated temperatures. Adding solid lubricant into micro-reservoirs produced by Laser Surface Texturing (LST) has been reported to decrease the coefficient of friction of sliding surfaces. In this study, incorporation of MoS2 and WS2 solid lubricants onto laser textured and ta-C coated steel surface by burnishing was demonstrated to provide improved tribological properties such as low friction and high wear resistance at elevated temperature with an extended lifetime of the surfaces.